Relationships between rural migration and perceptions of environmental change : Insights from Bushbuckridge, South Africa - Rusere, Farirai; Li, Quirui; Hunter, Lori; Collinson, Mark; Ouma, Stefan; Twine, Wayne; Samimi, Cyrus (Journal of Rural Studies, 2025)
Environmental change is increasingly threatening rural livelihoods across the globe. Yet rural communities possess valuable knowledge that could inform policy decisions on creating sustainable livelihoods amidst global environmental challenges and planning for rural community and landscape sustainability. Against this backdrop, this paper focuses on three key questions in a rural South African setting: What challenges do rural residents face in maintaining and developing livelihoods compared to the past? (ii) What environmental changes have they observed within their communities over their lifetime? and (iii) How are these changes perceived to influence circular migration for work? By examining rural dwellers’ perceptions of the challenges to securing sustainable livelihoods, valuable insights can be gleaned as to why certain strategies succeed while others fail, leading to the identification of areas for improvement in policy, programs and livelihood strategies. This study draws on qualitative data from focus group discussions held across nine villages in the MRC/Wits Agincourt Health and Socio-Demographic Surveillance System site in northeast South Africa. The facilitated focus group discussions allowed participants to reflect on a range of environmental and livelihood issues in relation to the study questions. The findings demonstrate that environmental stressors induced by climate change, pollution, and natural resource degradation are perceived to restrict employment and income opportunities, exacerbate water and food insecurity, and drive circular migration. These findings provide valuable insights for researchers and policymakers in crafting strategies to enhance adaptive capacity and mitigate the vulnerability of rural livelihoods in rural regions across the global South.
Keywords: Africa; community participation; environmental migration; Migration; rural livelihoods; South Africa